Transforming Educational Costs into Strategic Investments: Paving the Path for Global Competitiveness - Nur Indah; Indah Inayatur Rohmah (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Abstract This study examines the transformation of educational costs into strategic investments to enhance global competitiveness. Using a mix-method approach, data were collected through interviews, focus group discussions (FGDs), surveys, and document analysis in Indonesian educational institutions. The results show that strategic budget management can improve academic outcomes by up to 25%. Key challenges include a lack of transparency, limited managerial capacity, and insufficient public understanding. This strategy enhances access to education, learning quality, and students' global competitiveness. In conclusion, transforming educational costs into strategic investments supports improved educational quality, reduces socio-economic disparities, and fosters sustainable development. Keywords: Educational Investment, Global Competitiveness, Strategic Budget Management